Teknik Isolasi dan Kultur Protoplas Tanaman Padi - Deden Sukmadjaja; Novianti Sunarlim; Endang G. Lestari; Ika Roostika; Tintin Suharlini (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2007)
Protoplastfusion or somatic hybridization technology is an alternativetechnology for production hybrids of plants that are difficultto be produced by conventional methods due to their sexualincompatibility. An experiment was conducted to developtechniques for isolation, purification, and culture of riceprotoplasts of cultivar IR64 and a wild rice species (Oryzaofficinalis). Optimization of protoplast isolation and purificationmethods from both rice genotypes were successfullydone. The highest protoplast density was obtained bydigesting embryonic callus or stems of young seedling in anenzyme solution containing of 2% cellulose, 0.1% pectolyase,0.5% macerozyme, 0.5% driselase, 5 mM ES, and 13% mannitolin CPW solution. The protoplast digestion was done forthree hours by soaking in the enzyme solution followed byshaking at 50 rpm under a room temperature. Purification ofthe protoplasts were done by separating them from plantdebris using a 25% sucrose solution. Protoplast regenerationwas not successful using although different media compositionsand conditions. Growth process from cell division tocell aggregate was only successful on IR64 protoplast cultureon a medium that contained AgNO3.